INTENSITAS SERANGAN PENYAKIT VASCUAR STREAK VSD PADA BEBERAPA KLON KAKAO DI DESA SIDONDO III - N.Hi.Topae, Irwan Lakani, Johanis Panggeso, Febrianto (AGROTEKBIS, 2016)
This study aims to determine the intensity of the disease Vascular Streak Dieback (VSD) in some cocoa clones in the village of the District III Sidondo Sigi Biromaru. This study was conducted in cocoa plantations in the village of the District III Sidondo Sigi Biromaru 01 ° 06 01.9